Diagnostic efficacy of risk of malignancy index in adnexal mass: a prospective study - Anusha Kamath; Satyam Satyarth; Pariseema Dave (New Indian Journal of OBGYN, 2020)
Objectives: The purpose of this study was to determine if the risk of malignancy index (RMI 2) can distinguish between benign and malignant adnexal masses in the women with adnexal masses. Methods: This is a prospective observational study conducted over a period of two years from 2012 to 2014. A total of 100 cases of adnexal mass were selected using purposive sampling technique. Information regarding age, parity, menstrual status, history of previous surgery and symptoms were noted. RMI 2 was calculated for each patient. Statistical analysis was done using SPSS software version 21. Results: Majority (60%) of the women were in the perimenopausal or menopausal age group (40-60 years). Majority of the patients ie 62% had levels of CA-125 above100U/l, 16% had levels between 35-100U/l and 22% had levels <35 U/l. RMI was greater than 200 in 72% patients indicating malignancy and was less than 200 in 28% of the patients suggesting benign disease. The sensitivity of the RMI for diagnosing malignant lesions was 84% while the specificity was 67%. The PPV was 89% and the NPV was 57%. Conclusion: RMI appears to be a valuable, reliable and applicable method in the primary evaluation of patients with pelvic masses and a usable method in referral of relevant patients for centralised surgical treatment.